Endovascular treatment for sphenoidal region dural arteriovenous fistula - Yu, Jinlu (Frontiers in Neurology, 2024)
Sphenoidal region dural arteriovenous fistulas (DAVFs) are rare. Endovascular treatment (EVT) is an effective treatment approach. However, understanding and performing EVT for sphenoidal region DAVFs are difficult and challenging. Therefore, we performed a review to explore this issue further. In this review, we discuss the dural feeders and venous structures of the sphenoidal region, the angioarchitecture of sphenoidal region DAVFs, the role and principle of EVT, various EVT techniques, and the prognosis and complications associated with EVT. We found that various EVT techniques, including transarterial embolization (TAE), retrograde transvenous embolization (TVE), and direct puncture EVT, can be used to treat sphenoidal region DAVFs. TAE represents the most commonly utilized approach. TVE and direct puncture EVT should be limited to highly selective cases. EVT must penetrate the fistula and very proximal venous recipient pouch with a liquid embolic agent or coil the fistula point to have a curative effect completely. Successful EVT can lead to obliteration of sphenoidal region DAVFs and a good clinical outcome. However, these complications cannot be neglected.